The Concept Of Dialogue Among Civilizations - Malik, Ahmed Abdul; Mustaqimah, Mustaqimah; Sulaiman, Ibrahim Fahad (INTERNATIONAL CONFERENCE ON ISLAM STUDIES AND LOCAL WISDOM (ICISLOW), 2023)
Dialogue is “a communicative process in which people with different perspectives seek understanding.” To be in dialogue means that participants are not only engaging each other in light of their different views, but they are also striving to achieve a degree of mutual understanding. Based on the above definition, civilizational dialogue has been considered as a means to call people of different backgrounds, cultures, and civilizations toward mutual respect, humanity, and goodness and abstain them from discrimination, transgression, and evil deeds. But what exactly does the word ‘dialogue’ mean? What are the main types of dialogue? What is the process of dialogue? These questions will be answered in this paper using the descriptive method in other achieve a proper understanding of the concept. The research discovered that dialogue is a way for people with different perspectives to work together and to understand each other, and it plays a very significant role in a multicultural society to keep unity, struggling together toward a mutual objective.